2023
DOI: 10.3390/s23020696
|View full text |Cite
|
Sign up to set email alerts
|

Internet-of-Things-Enabled Markerless Running Gait Assessment from a Single Smartphone Camera

Abstract: Running gait assessment is essential for the development of technical optimization strategies as well as to inform injury prevention and rehabilitation. Currently, running gait assessment relies on (i) visual assessment, exhibiting subjectivity and limited reliability, or (ii) use of instrumented approaches, which often carry high costs and can be intrusive due to the attachment of equipment to the body. Here, the use of an IoT-enabled markerless computer vision smartphone application based upon Google’s pose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Computer vision (CV) is generally considered in two categories: 2D (a regular camera) and 3D (use of camera in conjunction with technologies such as infrared, e.g., Microsoft Kinect) [153]. CV has shown utility in providing insight into a variety of healthcare applications such as remote monitoring of vulnerable cohorts [154], fall detection [155,156], and running [157]. Typically, 3D-based CV is considered the gold standard in person identification due to its understanding of depth perception [158].…”
Section: Computer Vision and Gait Assessmentmentioning
confidence: 99%
“…Computer vision (CV) is generally considered in two categories: 2D (a regular camera) and 3D (use of camera in conjunction with technologies such as infrared, e.g., Microsoft Kinect) [153]. CV has shown utility in providing insight into a variety of healthcare applications such as remote monitoring of vulnerable cohorts [154], fall detection [155,156], and running [157]. Typically, 3D-based CV is considered the gold standard in person identification due to its understanding of depth perception [158].…”
Section: Computer Vision and Gait Assessmentmentioning
confidence: 99%
“…Commonly, the identification of these variables and parameters in clinical contexts is carried out through scales and tests [12,13]. Nowadays, due to the subjectivity of these tools [14], the use of instrumentation and/or technologies to increase their predictive value and objectivity has progressively been associated with their use [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that the majority of these tools are implemented in safe and controlled clinical contexts [14]. However, it has been observed that falls are influenced by various factors, with the environment being a significant determinant in their performance [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to other open-sourced 3D pose estimation libraries, such as OpenPose [19,25], BlazePose is computationally lightweight and can be deployed across various platforms, such as in a web browser as a JavaScript application. As a result of its versatility, BlazePose and other video-based pose estimation libraries have been used by researchers to develop different applications, including in the context of sports for movement abnormality detection [26], gait assessment [27], hypermobility assessment [28], yoga training [29], postural disorder monitoring for Parkinson's patients, [30] and spinal dysfunction risk estimation [31]. However, studies that explicitly examine the effectiveness of applying opensourced 3D pose-estimation library for range of motion evaluation remain scarce [32].…”
Section: Introductionmentioning
confidence: 99%